2001
DOI: 10.1063/1.1368164
|View full text |Cite
|
Sign up to set email alerts
|

Growth, structure, and transport properties of thin (>10 nm) n-type microcrystalline silicon prepared on silicon oxide and its application to single-electron transistor

Abstract: Microcrystalline silicon ( c-Si:H) thin films were prepared at 300°C on glass. Their structure and transport properties were studied in a wide range of film thickness ranging from 10 nm to 1 m. The crystal fraction increases monotonously from ϳ64% to ϳ100% as film thickness increases. Electron mobility first increases with increasing film thickness at thicknesses smaller than 50 nm but saturates at larger thickness. This mobility behavior is explained by percolation transport through crystalline grains. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…18 We have also observed in a study using poly-Si pointcontact devices that simple oxidation at 750°C, i.e., without the postannealing, does not change the electrical characteristics significantly but that postannealing at 1000°C in an Ar ambient increases the potential barrier height and the tunnel resistance. 18,19 It is known that thermal annealing of silicon suboxide induces phase separation into silicon and silicon dioxide, e.g., the process has been utilized to form nanocrystalline grains 20 or to fabricate ''separation by implanted oxygen'' substrates. 21 It is also reported that thermal annealing converts a partially oxidized SiϪSi n O 4Ϫn (nϽ4) tetrahedral structure to SiϪO 4 tetrahedral structure, confirmed by x-ray photoelectron spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…18 We have also observed in a study using poly-Si pointcontact devices that simple oxidation at 750°C, i.e., without the postannealing, does not change the electrical characteristics significantly but that postannealing at 1000°C in an Ar ambient increases the potential barrier height and the tunnel resistance. 18,19 It is known that thermal annealing of silicon suboxide induces phase separation into silicon and silicon dioxide, e.g., the process has been utilized to form nanocrystalline grains 20 or to fabricate ''separation by implanted oxygen'' substrates. 21 It is also reported that thermal annealing converts a partially oxidized SiϪSi n O 4Ϫn (nϽ4) tetrahedral structure to SiϪO 4 tetrahedral structure, confirmed by x-ray photoelectron spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce L grain overall, a nanocrystalline (nc) Si film prepared by a low-temperature very high frequency (VHF) plasma-enhanced chemical vapor deposition (PECVD) [26][27] was adopted instead of the SPC poly-Si films. A 20nm thick nc-Si:H film was prepared from a SiF 4 :H 2 :SiH 4 gas mixture at temperatures ≤ 300 °C.…”
Section: Optimisation Of Grain and Grain Boundaries Towards Room-tempmentioning
confidence: 99%
“…Among many production methods, plasma enhanced chemical vapor deposition (PECVD) is one of the useful techniques from the viewpoint of controllability of growth at atomic levels. Boufendi et al showed the growth of crystalline silicon fine particles with pulsed plasmas, 3 and Hayashi et al observed the growth of amorphous carbon layers on levitated seed amorphous carbon particles in rf CH 4 /H 2 plasmas. 8 In our previous study, we succeeded in levitating diamond seed particles in an rf CH 4 /H 2 plasma at the temperature of 1300 K for more than 10 h, and the island growth of diamond was observed on them.…”
Section: Introductionmentioning
confidence: 99%
“…Fine particles in the size of micro and nanometers are of great interests in many fields, e.g., thin film solar cells, 1, 2 quantum effect devices, 3,4 catalysis, 5 medicine, 6 electrodes for fuel cells, 7 etc. Those particles are designed to exhibit useful functions with relation to the material properties determined by fabrication methods and adopted conditions.…”
Section: Introductionmentioning
confidence: 99%